Case-Control Study of Paresthesia Among World Trade Center-Exposed Community Members. Issue 4 (April 2020) - Marmor, Michael; Thawani, Sujata; Cotrina, Maria Luisa; Shao, Yongzhao; Wong, Ericka S.; Stecker, Mark M.; Wang, Bin; Allen, Alexander; Wilkenfeld, Marc; Vinik, Etta J.; Vinik, Aaron I.; Reibman, Joan
Abstract : Objective: To investigate whether paresthesia of the lower extremities following exposure to the World Trade Center (WTC) disaster was associated with signs of neuropathy, metabolic abnormalities, or neurotoxin exposures. Methods: Case-control study comparing WTC-exposed paresthesia cases with "clinic controls" (WTC-exposed subjects without paresthesias), and "community controls" (WTC-unexposed persons). Results: Neurological histories and examination findings were significantly worse in cases than controls. Intraepidermal nerve fiber densities were below normal in 47% of cases and sural to radial sensory nerve amplitude ratios were less than 0.4 in 29.4%. Neurologic abnormalities were uncommon among WTC-unexposed community controls. Metabolic conditions and neurotoxin exposures did not differ among groups. Conclusions: Paresthesias among WTC-exposed individuals were associated with signs of neuropathy, small and large fiber disease. The data support WTC-related exposures as risk factors for neuropathy, and do not support non-WTC etiologies. Abstract : Supplemental Digital Content is available in the text